The Influence Of Social Media As A Trigger For Depression In Women: A Critical Discourse Analysis Study - Rd Bily Parancika; Mohammad Aris; Erwin Setyawan (JUPE : Jurnal Pendidikan Mandala, 2026)
This research is a descriptive research. Participants in this study were women who used social media in their daily lives, aged 20-40 years. The data collection methods carried out in this study are: observation, questionnaire, and literature study. The sampling technique is used randomly or randomly. The data used in this study is the upload that has the most likes from Instagram social media @rat_naah with the number of Instagram followers as many as 15,000 people. The results of the analysis in this study use Norman Fairclough's critical discourse analysis of text types, to determine the form of representation, relationship and identity of account owners described in semantic linguistic studies in forming meaning in sentences. This study shows that social media has a very significant influence in triggering depression in women, due to negative events that occur repeatedly and continuously.